Differences in US-German time-allocation: Why do Americans work longer hours than Germans? - Ronald Schettkat (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
The conventional view is that Americans work longer hours than Germans and other Europeans but when time in household production is included, overall working time is very similar on both sides of the Atlantic. Americans spend more time on market work but German invest more in household production. This paper examines whether these differences in the allocation of time can be explained by differences in the incentive structure, this is by the tax-wedge and differences in the wage differentials, as economic theory suggests. Its analysis of unique time-use data reveals that the differences in time-allocation patterns can indeed be explained by economic variables. – – Nach allgemeiner Auffassung arbeiten Amerikaner länger pro Jahr als Deutsche oder andere Europäer. Wenn jedoch die Arbeit im Haushalt einbezogen wird, ist die Gesamtarbeitszeit auf beiden Seiten des Atlantiks fast gleich. Amerikaner leisten mehr Arbeitsstunden in bezahlter Arbeit, Deutsche investieren mehr Arbeitsstunden in Hausarbeit. Dieser Beitrag untersucht, ob diese unterschiedliche Arbeitszeitverteilung durch unterschiedliche Anreizstrukturen erklärt werden kann; das heißt Steuerzwänge und Lohn-/Gehaltsunterschiede, wie dies wirtschaftstheoretische Überlegungen nahe legen. Die Analyse von zeitgleichen Daten ergibt, dass Arbeitszeitverteilungsmuster tatsächlich durch ökonomische Variablen erklärt werden können.
Keywords: 330; Arbeitszeit; Hausarbeit; Zeitallokation; Haushaltsproduktion; Steuerbelastung; Lohnstruktur; USA; Deutschland